IMPLEMENTASI MENTORING PADA MATERI PENDIDIKAN AGAMA ISLAM KELAS VIII DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU MUTIARA INSAN SUKOHARJO TAHUN 2025/2026 - Fadhilah Imtinan Daru Ekowati; Ngatmin Abbas; Arif Effendi (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of mentoring in Islamic Religious Education (PAI) learning for eighth-grade students at SMPIT Mutiara Insan Sukoharjo in the 2025/2026 academic year. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research informants consisted of Islamic Religious Education teachers, mentors, homeroom teachers, and eighth-grade students participating in mentoring activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while triangulation techniques were used to ensure data validity. The results showed that the mentoring program was implemented through small groups (halaqah) consisting of opening activities, material delivery, interactive discussions, and evaluation of students’ worship practices. The mentoring program had a positive impact on students’ understanding of Islamic Religious Education materials and the development of religious character. The obstacles encountered included limited time, differences in students’ characteristics and abilities, and uneven mentor competence. Efforts to overcome these obstacles were carried out through mentor training, the use of varied learning methods, and strengthening motivation and school support. Therefore, mentoring can be considered an effective strategy for improving the quality of Islamic Religious Education learning.